(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article provides information on improving students’ healthy lifestyle content based on creative approaches, promoting healthy lifestyles, providing students and adults with certain medical and hygienic knowledge of a healthy lifestyle, and awakening their perceptions of how a healthy lifestyle affects the development of the body.